Calcitropic Hormones and Metabolic Markers Differ in Young South Asian Indian Men and Caucasians (P04-119-19). (13th June 2019) - Ramadoss, Rohit; Altasan, Asma; Cheung, May; DeLuccia, Rosemary; Sukumar, Deeptha; Aljahdali, Abeer
Abstract: Objectives: The incidence rate of metabolic syndrome is higher in South Asian Indians (SAI) and is generally accompanied by changes in calcitropic hormones. Typically, these findings are reported in middle age or older adults and data in a younger population is scarce. The purpose of the study was to analyze the differences in calcitropic hormones and metabolic markers in younger South Asian Indian and Caucasian men Methods: Caucasian or South Asian Indian men between 21–41 years of age were recruited for this study. Anthropometric measurements such as weight (kg), height (cm) and waist circumference (cm) were obtained. An 8-hour fasting blood sample was collected for analysis of serum concentrations of 25 hydroxyvitamin D (25OHD), parathyroid hormone (PTH), C-reactive protein (CRP), osteocalcin (OC), high molecular weight (HMW) adiponectin, glycemic indices, and lipid profile. Independent sample t-tests were used to report the mean differences between groups. The significance level was set for P < 0.05. Results: A total of 26 men (13 SAIs and 13 Caucasians) completed the study. The mean age for SAI men was 27.82 ± 5.64 y and 27.39 ± 5.29 y for Caucasian men. Body mass index (BMI) averaged at 25.93 ± 3.97 kg/m 2 for SAIs and 26.44 ± 2.49 kg/m 2 for Caucasians. Serum 25(OH)D concentrations were lower in the SAI men (21.58 ± 8.11 ng/mL) compared to Caucasian men (29.14 ± 7.17 ng/mL) ( P = 0.019 ). Serum concentrations of PTH were higher ( P = 0.007 ) in the SAI men (72.39 ± 24.32 pg/mL) compared to Caucasian Men (45.30 ± 21.95 pg/mL). Furthermore, HMW adiponectin was significantly lower ( P = 0.008 ) in SAIs (2.00 ±1.29 mg/L) compared to Caucasians (3.95 ± 2.01 mg/L). Glycemic indices, inflammatory markers, serum osteocalcin, and lipid profiles were not different between groups. Conclusions: These results show that differences in calcitropic hormones are observed in young South Asian Indian men compared to Caucasians although differences in metabolic parameters do not exist at this point. Changes in calcitropic hormones may provide early insight into the development of metabolic syndrome in this population. Intervention studies should address whether correction of vitamin D status will delay the development of metabolic syndrome in this population. Funding Sources: CNHP Seed Funding.